Associations of Usual Pace and Complex Task Gait Speeds With Incident Mobility Disability. Issue 10 (18th July 2019) - Rosso, Andrea L.; Metti, Andrea L.; Faulkner, Kimberly; Brach, Jennifer S.; Studenski, Stephanie A.; Redfern, Mark; Rosano, Caterina
Abstract : BACKGROUND/OBJECTIVES: To assess whether gait speed under complex conditions predicts long‐term risk for mobility disability as well as or better than usual‐pace gait speed. DESIGN: Longitudinal cohort study. SETTING/PARTICIPANTS: Subsample of Health Aging and Body Composition study with follow‐up from 2002 to 2003 to 2010 to 2011, including 337 community‐dwelling adults (mean age = 78.5 years, 50.7% female, 26.1% black). MEASUREMENTS: Associations of gait speed measured under usual‐pace, fast‐pace, dual‐task, and narrow‐path conditions with mobility disability, defined by any self‐reported difficulty walking ¼ mile assessed annually, were tested by Cox proportional hazard models adjusted for demographic and health characteristics. Models were fitted for each walking condition, and R 2 statistics were used to compare predictive value across models. Models were repeated for persistent mobility disability, defined as at least two consecutive years of mobility disability. RESULTS: Mobility disability occurred in 204 (60.5%) participants over the 8‐year follow‐up. There was a lower hazard of developing mobility disability with faster gait speed under all conditions. Hazard ratios, confidence intervals, and R 2 of gait speed predicting mobility disability were similar across all four walking conditions ( R 2 range = 0.22‐0.27), but were strongest for dual‐task gait speed (hazard ratio [95% confidence interval], R 2 of fully adjusted models = 0.81 [0.75‐0.88], 0.27). Results were comparable for persistent mobility disability ( R 2 range = 0.26‐0.28). CONCLUSION: Slower gait speed under both usual‐pace and complex conditions may be a clinical indicator of future risk of mobility disability. These results support the call for increased use of gait speed measures in routine geriatric care. J Am Geriatr Soc 67:2072–2076, 2019